Engagement acadêmico : contributos das tecnologias digitais para um processo [trans]formativo nas relações de engajamento na Educação Superior - Rigo, Rosa Maria (2020)
This doctoral dissertation investigates academic engagement in higher education, focusing on first year university students with a scope of bringing Portugal and Brazil closer together. Engagement is identified as the most influential transversal variable in terms of learning and adherence to studies in the international context, revealing itself to have a multiplicity of meanings, capable of bringing together numerous aspects due to different types of engagement (personal, moral, social, professional, identity, academic, relational). In this study, academic engagement is understood as the construction of new educational paradigms based on the need to adapt teaching to the demands of the 21st century and awareness of the continuities, changes, and challenges in university policies that such an understanding represents. Our research question is: What are the most influential factors for promoting engagement of first year undergraduate students? The guiding questions elaborated for the research are: What are the recurring principles found in this area’s literature regarding aspects that promote student engagement in the first two semesters of university? How are the academic, classroom, technological, and campus environments addressed in the first year at the university? What actions are proposed by institutions to engage incoming undergraduates? Theoretical contributions include Audy and Morosini (2009, 2010), Chickering and Gamson (1987), Coates (2005, 2006, 2007, 2008, 2009, 2010, 2011), Coates and Ranson (2011), Fredricks, Blumenfeld and Paris (2004), Moreira, Barros and Monteiro (2015), Trindade and Moreira (2017), Krause (2005, 2006, 2008), Trowler and Trowler (2010), OECD (2018). The study adopts a qualitative and quantitative approach. Data collection instruments include an online questionnaire and bibliographic research. The primary results indicate that the factors that favor academic engagement include: 1) Interpersonal Relations (colleagues); 2) Academic Development (attitudes, personality, didactics, teacher involvement and commitment); 3) Digital Technologies, 4) Infrastructure (classrooms, campus areas, spaces for research, spaces for food, library, convenience and easy access to the university environment); 5) Personal Development (focus, dedication, discipline, willpower, interest of the students themselves); 6) Academic Support (Support sectors); 7) Content (content that provides multidimensional learning); 8) Leisure Areas (spaces for rest); 9) Feeling of belonging (students’ feeling that they are a part of something bigger).